A Critical Exegesis of Maine's Creaky Tax Code - Mills, Peter (Maine Policy Review, 1997)
In this provocative and thorough examination of Maine's tax code, Peter Mills provides a candid assessment of what is wrong with the state’s current system. Focusing on the revenue side of state government, Mills begins by pointing out that Maine does not have a cohesive tax code per se, but a hodgepodge of provisions and exemptions that in totality place the primary burden for supporting state government on the labor and consumption of Maine's individual citizens. Mills offers his own perspective on fixing the troubled tax code, and suggests some solutions such as reducing the sales tax rate and eliminating the BETR/TIF "double dip." In proposing such changes, Mills challenges legislators and other state leaders to transcend political expediency in fixing the many problems he raises for discussion.
Keywords: Maine tax code; Maine tax reform